MBR공정에서 질산화 미생물고정화 담체 적용에 따른 막 오염 제어 - 김지숙(Ji Sook Kim); 국영롱(Young Long Kuk); 박정연(Jung Yeon Park); 장유정(You Jung Jang); 박철휘(Chul hwi Park) (Daehan hwan'gyeong gonghag hoeji, 2019)
MBR 공정에 있어 막 오염을 제어하기 위하여 임계플럭스 하향 운전, 유입수 전처리 및 막 세정(공기 세정, 역 세척, 화학 세정)을 하는데 막 세정에 의한 에너지 소비가 높아 막 오염 제어와 동시에 에너지 소비 저감에 대한 대책이 필요하다. Scouring agent로 공기 외에 입상 물질을 적용하면 막 오염 제어를 증가시키고, 공기세정을 줄일 수 있어 에너지 측면에서 효율적이다. 본 연구에서는 PVA재질의 nitrifier immobilized media를 scouring agent로 적용함으로써 막 오염을 저감시키고, 고농도의 MLSS를 대체할 수 있어 막 표면 및 공극을 막는 EPS 및 SMP등의 막 오염 유발 인자를 줄일 수 있다. Flux 17, 21, 24 L/m2/h조건에서 막 차압 상승률을 비교한 결과, 17 L/m2/h에서는 MBR과 MMBR의 차이가 거의 없었지만, 21, 24 L/m2/h에서는 MBR의 차압은 242%, 485%까지 상승하였고 MMBR은 66.5%, 225%로 MMBR의 차압 상승률이 2배 이상 낮은 것을 확인하였다. 실험 기간 동안 원수의 NH3-N농도가 평균 115 mg/L일 때 HRT 6 h 조건에서 MBR, MMBR 모두 100% 질산화되었다. In order to control membrane fouling in the MBR process, energy consumption by membrane cleaning is high as critical flux down operation, influent pre-treatment, and membrane cleaning (air cleaning, back washing, chemical cleaning) needs to be taken to control membrane fouling and reduce energy consumption at the same time. It is energy - effective to apply granular materials as scouring agent other than air to increase membrane fouling control and reduce the amount of air. In this study, nitrifier immobilized media of PVA material can be applied as scouring agent to reduce membrane fouling and it is possible to replace the MLSS of high concentration, which can reduce membrane fouling factors such as EPS and SMP that inducing membrane pore blocking. The transmembrane pressure difference was analyzed in case of flux 17 L/m2/h and 21, 24 L/m2/h respectively, there was almost no difference between the MBR and MMBR in the flux 17 L/m2/h but the pressure of 21, 24 L/m2/h increased to 242%, 485% in MBR and increased 64%, 225% in MMBR. Also, high concentration of NH3-N over 100 mg/L was 100% nitrified all together at HRT 6 h. KCI Citation Count: 2